Under-deposit corrosion of tubing served for injection and production wells of CO2 flooding. (September 2021) - Wang, Qiuyu; Wu, Wei; Li, Qing; Zhang, Deping; Yu, Yifan; Cao, Bei; Liu, Zhiyong
Highlights: The under-deposit corrosion mechanism of tubing steel is clarified in detail. The synergistic effect of CO2 and SRB causes under-deposit corrosion. The enrichment of Cl - accelerates the localized corrosion process beneath the corrosion products. Abstract: The tubing steel served for the injection and production wells of CO2 flooding was investigated using various characterization methods. The results showed the corrosion failure of the tube was caused by the jointed action of sulfate-reducing bacteria (SRB), CO2 and chloride ions ( Cl - ) during service. The corrosion product film formed on the tubing steel exhibited a bilayer structure. The outer layer was mainly composed of FeS and FeCO3, which was caused by SRB corrosion and CO2 corrosion respectively, and the inner layer was primarily iron oxide and oxyhydroxide caused by Cl - enrichment and CO2 corrosion. FeCO3 was found in both layers. Accordingly, the synergistic effect of SRB and CO2 resulted in the under-deposit corrosion, and the enrichment of Cl - accelerated the localized corrosion.